A generalization of generalized Fibonacci and generalized Pell numbers. Issue 1 (2nd January 2017) - Abd-Elhameed, W.M.; Zeyada, N.A.
Abstract : This paper is concerned with developing a new class of generalized numbers. The main advantage of this class is that it generalizes the two classes of generalized Fibonacci numbers and generalized Pell numbers. Some new identities involving these generalized numbers are obtained. In addition, the two well-known identities of Sury and Marques which are recently developed are deduced as special cases. Moreover, some other interesting identities involving the celebrated Fibonacci, Lucas, Pell and Pell–Lucas numbers are also deduced.